Hubungan Kelayakan Kendaraan Sepeda Motor Dan Kualitas Pelayanan Terhadap Kepuasan Konsumen - Muhammad Fhareza Deri; Annio Indah Lestari Nasution; Juliana Nasution (Jurnal Ekonomi, 2025)
This study aims to analyze the relationship between motorcycle roadworthiness and service quality on the level of satisfaction of inDrive online motorcycle taxi users in Medan. In the midst of the advancement of the digital era, online transportation services such as inDrive have become a vital element in supporting urban mobility. Customer satisfaction is a crucial aspect for service providers in maintaining sustainability and driving business growth. A quantitative approach with a cross-sectional research design was used in this study, involving 96 participants who have used inDrive services in Medan. The research findings show that both aspects of vehicle roadworthiness and service quality have a significant relationship with customer satisfaction. Based on these results, it is recommended that inDrive pay more attention to regular vehicle maintenance to enhance the user experience, improve driver service quality, and listen to customer feedback. These steps are expected to increase customer satisfaction, strengthen loyalty, and ultimately, expand inDrive's market share amidst increasingly fierce industry competition.